Investigations of Lead Free Halides in Sodium Based Double Perovskites Cs2NaBiX6(X=Cl, Br, I): an Ab Intio Study - Choudhary, Shaily; Tomar, Shalini; Kumar, Depak; Kumar, Sudesh; Verma, Ajay Singh (East European Journal of Physics, 2021)
Despites the excellent merits of lead based perovskite optoelectronic devices; their unstable nature and toxicity still present a bottleneck for practical applications. Double perovskite has emerged as a candidate for optoelectronics and photovoltaic application because of its nontoxic behaviour and stability in air. We have presented ab-initio study of Cs2NaBiX6(X=Cl, Br, I) lead free halide double perovskites. The calculation is carried out using the FP-LAPW method in the DFT framework within PBE potential using the WIEN2k code. The structural, electronic and optical properties of Cs2NaBiI6, Cs2NaBiBr6 and Cs2NaBiCl6 have been analysed. We have obtained the band gap of 2.0, 2.6 and 3.7 for Cs2NaBiI6, Cs2NaBiBr6 and Cs2NaBiCl6 respectively. Throughout the study, we have shown that the variation in the structure of double perovskite within Cs2NaBiX6(X=Cl, Br, I) that leads to the variation in band gap, density of states and in optical properties such as extinction coefficient, absorption spectra, optical reflectivity, dielectric coefficient, refractive index that shows the variety of this material for optoelectronic devices and other purposes.